Incidence, predictive factors, and clinical impact of stent recoil in stent fracture lesion after drug-eluting stent implantation. (1st July 2016) - Ohya, Masanobu; Kadota, Kazushige; Kubo, Shunsuke; Tada, Takeshi; Habara, Seiji; Shimada, Takenobu; Amano, Hidewo; Izawa, Yu; Hyodo, Yusuke; Otsuru, Suguru; Hasegawa, Daiji; Tanaka, Hiroyuki; et al.
Abstract: Background: Stent fracture (SF) after drug-eluting stent (DES) implantation was reported to be associated with target lesion revascularization (TLR). We have noted abnormal late acquired stent axial deformation in lesions after DES implantation, especially in SF lesions, and defined it as stent recoil (SR). We evaluated the incidence, predictive factors, and clinical impact of SR in SF lesions. Methods: Between 2003 and 2012, 5456 patients (11, 712 lesions) underwent DES implantations and follow-up angiography within one year after the index procedure. SR was defined as an axial recoil deformation less than 80% of the stent diameter and SF was defined as the separation of stent segments or stent struts. SF and SR were confirmed by follow-up angiography. The primary endpoint was defined as clinically driven TLR. Results: SF was observed in 494 lesions (4.2%) and SR in 138 of SF lesions (27.9%). According to multinomial logistic regression analyses, severe calcification and ostial lesion in the right coronary artery were stronger predictive factors of SF with SR lesions. The cumulative incidences of any and clinically driven TLR at 5 years were both significantly higher in the SF with SR group than in the SF without SR group (51.7% versus 35.0%, P < 0.001; 22.2% versus 12.8%, P = 0.019; respectively). Conclusions: SR in SF lesions after DES implantation could be related to the lesion characteristics. SF with SR was highly associated with subsequent TLR compared with SF without SR.